1329 Can One Size Fit All: Is Laparoscopic Roux-En-Y Gastric Bypass the Best Bariatric Procedure for Treating Type 2 Diabetes Mellitus (T2DM)?. (12th October 2021) - Mahendran, V; Ricart, P; Robinson, S; Perry, A; Wadley, M
Abstract: Introduction: Bariatric surgery produces superior weight loss and reversal of comorbidities in morbidly obese individuals compared to medical therapy alone. Laparoscopic Roux-en-Y gastric bypass (LRYGB) was traditionally considered to prolonged remission of T2DM compared to other procedures such as Laparoscopic Sleeve-Gastrectomy (LSG). But recently published studies seek to disprove this by emphasising on duration and severity of T2DM before surgery rather than the type of procedure. We aim to verify if the severity of T2DM and type of operation (LRYGB Vs LSG) influence remission rates. Method: In this retrospective cohort study, 204 patients were diagnosed with T2DM pre-operatively and had undergone either LRYGB or LSG. We used the Individualised Metabolic Surgery Score (IMSS) tool to divide patients into mild, moderate, and severe categories. Results: Results showed that of the 204 patients 15% (n = 31) had mild disease, 62%( n = 127) had moderate disease and 23% (n = 46) had severe disease. Remission rates in each category were as follows: Mild: LSG (n = 17)100%; LRYGB (n = 14) 100% Moderate: LSG (n = 37) 69.4%; LRYGB (n = 90) 82.6% Severe: LSG (n = 11) 0%; LRYGB (n = 35) 21.4% Conclusions: We agree that patients with longstanding and severe T2DM have low remission rates after bariatric surgery, probably due to diminished beta-cell reserve. It is in contrary to recent publications which recommend LSG over LRYGB in patients with severe disease. This evidence necessitates further prospective studies before deciding which is the best procedure for patients with severe and longstanding T2DM.